Evaluation of Pediatricians’ and General Dentists’ Knowledge and Attitudes toward Infant Oral Health in the Delhi NCR Region - Tushar Pruthi; Nikhil Srivastava; Vivek Rana; Noopur Kaushik; Navpreet Kaur; Sakshi Gaind (The Bioscan, 2025)
Background: Dental health needs to be constructed with oral health as its cornerstone. Infants are examined by paediatricians multiple times in the first and second years of life. For guidance on ensuring their child's appropriate growth and development, parents typically consult physicians. This study aimed to educate parents on the importance of preventive oral health care (OHC) for infants and to assess the attitudes and knowledge of pediatricians and general dentists regarding infant oral health. Materials and methods: A total of 200 paediatricians and 200 general dentists practicing in the Delhi/NCR region were randomly selected to participate in this cross-sectional study. Participants were provided with a structured, objective questionnaire assessing their knowledge and attitudes toward infant oral health care (OHC). The questionnaire was administered without offering any prior information or guidance related to dental health, ensuring unbiased responses. Results: Statistical analysis was performed using the paired t-test to evaluate differences between general dentists and pediatricians. To ensure the reliability and agreement of the questionnaire responses, Kappa statistics were also applied. Conclusion: Paediatricians demonstrated comparatively limited knowledge regarding infant oral health when compared to general dentists. This highlights the need for enhanced oral health education and interdisciplinary collaboration to ensure timely and effective dental care for infants. a structured, objective questionnaire assessing their knowledge and attitudes toward infant oral health care (OHC). The questionnaire was administered without offering any prior information or guidance related to dental health, ensuring unbiased responses. Results: Statistical analysis was performed using the paired t-test to evaluate differences between general dentists and pediatricians. To ensure the reliability and agreement of the questionnaire responses, Kappa statistics were also applied. Conclusion: Paediatricians demonstrated comparatively limited knowledge regarding infant oral health when compared to general dentists. This highlights the need for enhanced oral health education and interdisciplinary collaboration to ensure timely and effective dental care for infants.